2015
DOI: 10.1016/j.bbrc.2015.01.158
|View full text |Cite
|
Sign up to set email alerts
|

Isoaspartate, carbamoyl phosphate synthase-1, and carbonic anhydrase-III as biomarkers of liver injury

Abstract: We had previously shown that alcohol consumption can induce cellular isoaspartate protein damage via an impairment of the activity of protein isoaspartyl methyltransferase (PIMT), an enzyme that triggers repair of isoaspartate protein damage. To further investigate the mechanism of isoaspartate accumulation, hepatocytes cultured from control or 4-week ethanol-fed rats were incubated in vitro with tubercidin or adenosine. Both these agents, known to elevate intracellular S-adenosylhomocysteine levels, increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
2
12
0
1
Order By: Relevance
“…The downregulation of Ca3 levels by the treatment of ethanol and a hepatotoxicant of carbon tetrachloride was also reported124849. The depletion of Ca3 is also a useful biomarker for liver injury50. The usefulness of downregulated Ca3 levels for identifying NGHCs has also been demonstrated in this study.…”
Section: Resultssupporting
confidence: 72%
“…The downregulation of Ca3 levels by the treatment of ethanol and a hepatotoxicant of carbon tetrachloride was also reported124849. The depletion of Ca3 is also a useful biomarker for liver injury50. The usefulness of downregulated Ca3 levels for identifying NGHCs has also been demonstrated in this study.…”
Section: Resultssupporting
confidence: 72%
“…Carbonic anhydrase 3 promotes transformation and 343 invasion capability in hepatoma cells through FAK signaling pathway [60] and is a major 344 participant in the liver response to oxidative stress [61] . Carbonic anhydrase 3 is also a 345 biomarker of liver injury [62] . Thioredoxin has a potential to attenuate liver fibrosis via 346 suppressing oxidative stress and inhibiting proliferation of stellate cells [63] and plays 347 important roles in the pathophysiology of liver diseases [64] .…”
mentioning
confidence: 99%
“…To minimize the affecting 62 factors, animal models can be used for urinary biomarker discovery of liver fibrosis [34] .…”
mentioning
confidence: 99%
“…In this light, an experimental study done by Carter et al. revealed that the levels of cytosolic CPS1 increased in conjunction with the duration of alcohol consumption in ethanol‐fed rats. This implied its potential use as a measure for the extent or length of exposure of the liver to stress.…”
Section: Discussionmentioning
confidence: 95%